1‐Phenyl‐3‐pentanone, a Volatile Compound from the Edible Mushroom Mycoleptodonoides aitchisonii Active Against Some Phytopathogenic Fungi. Issue 7 (22nd March 2013) - Nishino, Shigeki; Parada, Roxana Y.; Ichiyanagi, Tsuyoshi; Maekawa, Nitaro; Shimomura, Norihiro; Otani, Hiroshi
Abstract Volatiles produced by mycelia of mushrooms with aromatic odour were investigated for their antifungal activity against plant‐pathogenic fungi. The results of the screening of 23 species of basidiomycetes revealed that volatile substances from mycelia of Mycoleptodonoides aitchisonii (TUFC10099), an edible mushroom, strongly inhibited the mycelial growth, spore germination and lesion formation on host leaves of some plant‐pathogenic fungi including Alternaria alternata, A. brassicicola, A. brassicae, Colletotrichum orbiculare and Corynespora cassiicola. The volatile compounds were isolated from the culture filtrate of M. aitchisonii, and 1‐phenyl‐3‐pentanone was identified as a major antifungal volatile. The compound had significantly inhibitory activity against plant‐pathogenic fungi at 35 ppm. This is the first report that the volatile compound produced by mycelia of M. aitchisonii has antifungal activity against plant‐pathogenic fungi.